2006
DOI: 10.1063/1.2190459
|View full text |Cite
|
Sign up to set email alerts
|

Simple fabrication of a ZnO nanowire photodetector with a fast photoresponse time

Abstract: A zinc oxide ͑ZnO͒ nanowire photodetector was fabricated by a simple method of growing ZnO nanowires bridging the gap of two patterned zinc electrodes. The nanowire growth is self-catalytic, involving the direct heating of patterned Zn electrodes at 700°C in an O 2 / Ar gas flow of 20 SCCM ͑standard cubic centimeter per minute at STP͒/80 SCCM, respectively, at atmospheric pressure for 3 h. The fabricated photodetector demonstrated fast response of shorter than 0.4 ms to UV illumination in air, which could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
227
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(239 citation statements)
references
References 19 publications
12
227
0
Order By: Relevance
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…Room-temperature ultraviolet lasing [12] and piezoelectric nanogenerators based on ZnO nanowire arrays have been demonstrated [13]. Rectifying diodes of single ZnO nanobelt/nanowire-based devices [14] and a ZnO nanowire photodetector [15] were fabricated very recently.…”
mentioning
confidence: 99%
“…Many materials and structures including quantum dots [90][91][92], nanotubes [93][94][95][96], and nanowires [97][98][99] have been studied and considered to be good alternatives for silicon-based photodetectors. Interestingly, most of the 2D semiconductors are sensitive to light, heat, and ambient which makes them very attractive for applications in optoelectronic device sensing from infrared to the ultraviolet regime.…”
Section: Photodectorsmentioning
confidence: 99%